Buttonless : incredible iPhone and iPad games and the stories behind them - Rigney, Ryan (CRC Press, 2012)
"If you own an iPhone, iPod, or iPad and are interested in gaming, then this book will be your absolute best resource. Written by an established video game journalist and with contributions from leading gamers, the book presents some of the most interesting iPhone and iPad games, along with stories of the people behind these games. It describes hundreds of titles, including well-known games and hidden gems. An excellent resource for serious gamers, the book provides insight into the development of games for the iOS platform. "-- Provided by publisher